ANALISIS MAKNA KEBERLANJUTAN (RENZOKU) PADA SETSUZOKUJOSHI TE KARA DAN TA ATODE (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2018)
In Japanese language, there are particles (joshi) connect word to word, and also clause to clause, called setsuzokujoshi. The excessive number of particles and similar characteristic of some setsuzokujoshi cause those particles perplexing to use. For instance, te kara dan ta atode, both are different but yet similar. These two setsuzokujoshi are expressions that are taught in beginner level of Japanese language learning, and commonly known that distinguish in ‘time’ at which the two clauses occur. This paper identified these two setsuzokujoshi in relation to the ‘continuity’ nuance meaning, as what Mizuno (2001) has stated that te kara carries the ‘connection’ nuance while ta atode carries ‘disconnection’ nuance to the clauses they connect. The methodology used in this paper is descriptive qualitative analysis method through analysing both the primary data and secondary data based on the research of Mizuno (2001). The primary data used in this research is taken from a website which provides recipes in Japanese language.